2018
DOI: 10.1002/bjs.10670
|View full text |Cite
|
Sign up to set email alerts
|

Carotid plaque volume in patients undergoing carotid endarterectomy

Abstract: BackgroundThe main indication for carotid endarterectomy (CEA) is severity of carotid artery stenosis, even though most strokes in carotid disease are embolic. The relationship between carotid plaque volume (CPV) and symptoms of cerebral ischaemia, and the measurement of CPV by minimally invasive tomographic ultrasound imaging, were investigated.MethodsThe volume of the endarterectomy specimen was measured using a validated saline suspension technique in patients undergoing CEA. Time from last symptom and seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 48 publications
1
19
0
5
Order By: Relevance
“…As part of a major study on the importance of carotid plaque volume (CPV) as a cause of cerebral ischemia, 23 we also explored of the role of resistance to aspirin and clopidogrel in patients admitted for carotid endarterectomy. Our aim was to determine whether resistance to platelet-inhibitory therapy related to the number of cerebral emboli detected in the ipsilateral middle cerebral artery (MCA) by TCD pre-operatively and recent symptoms of cerebral ischemia.…”
Section: Aimsmentioning
confidence: 99%
“…As part of a major study on the importance of carotid plaque volume (CPV) as a cause of cerebral ischemia, 23 we also explored of the role of resistance to aspirin and clopidogrel in patients admitted for carotid endarterectomy. Our aim was to determine whether resistance to platelet-inhibitory therapy related to the number of cerebral emboli detected in the ipsilateral middle cerebral artery (MCA) by TCD pre-operatively and recent symptoms of cerebral ischemia.…”
Section: Aimsmentioning
confidence: 99%
“…Introduction -Carotid Plaque Volume (CPV) correlates more closely than severity of stenosis with symptoms of cerebral ischemia in patients with carotid disease [1]. If we could measure CPV by a minimally-invasive technique, it may replace severity of stenosis as the principle indication for carotid endarterectomy (CEA) and may even be used for population screening in the future.…”
Section: O-094 Can Carotid Plaque Volume Be Measured By 3d Tomographimentioning
confidence: 99%
“…Risk stratification for carotid stenosis generally has been based on angiographic or Doppler ultrasonographic examination of luminal stenosis but we need to identify vulnerable carotid plaque by using more sophisticated methods such as positron emission tomography with computed tomography, magnetic resonance imaging (MRI), contrast enhanced ultrasound techniques and detection of micro-embolism using transcranial Doppler (TCD) ultrasound (45)(46)(47)(48)(49)(50) . The pattern of progression of carotid stenosis is unpredictable and it may progress rapidly or slowly or remain stable in long term period (46) .…”
Section: How Can We Identify Vulnerable Carotid Plaque?mentioning
confidence: 99%
“…Measuring carotid plaque volume (CPV) by minimally invasive tomographic ultrasound imaging and MRI suggested that CPV was associated with cardiovascular risk factors and symptoms of cerebral ischemia (50,51) . Ball et al (50) reported that CPV correlated with symptoms of cerebral ischemia but not carotid stenosis and it could be a potential indicator for CEA.…”
Section: How Can We Identify Vulnerable Carotid Plaque?mentioning
confidence: 99%
See 1 more Smart Citation